2019
DOI: 10.1002/fsn3.1134
|View full text |Cite
|
Sign up to set email alerts
|

Enriched bovine IgG fraction prevents infections with Enterohaemorrhagic Escherichia coli O157:H7, Salmonella enterica serovar Enteritidis, and Mycobacterium avium

Abstract: A bovine IgG‐enriched whey fraction contains antibodies against various bacterial antigens. We investigated the protective effects of a bovine whey fraction preparation against infections with Enterohaemorrhagic Escherichia coli O157:H7, Salmonella enterica serovar Enteritidis, and Mycobacterium avium in mouse models. After infection with these pathogens, the IgG‐enriched fraction or skim milk was given ad libitum at a 5% solution instead of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Additional studies are needed to better understand the mechanism behind the immunomodulatory action. The oral administration of BC IgG-enriched whey fractions (IgG25+) has the potential to protect against food-borne infections ( Salmonella enterica serovar Enteritidis, Enterohaemorrhagic Escherichia coli O1 57:H7, Mycobacterium avium ) and was also found to be partially effective against respiratory tract infection in mice [ 120 ]. Sanctuary et al [ 30 ] reported that the supplementation of bovine colostrum oligosaccharides with Bifidobacterium longum subspecies Infanti 0.3 g twice/day for 12 weeks to children of age 2–11 years suffering from gastrointestinal symptoms and autism disorders results in improvement of gastrointestinal (GI) symptoms and is well-tolerated with a mild gassiness as a common side effect.…”
Section: Current Evidence Of Therapeutic Use Of Bcmentioning
confidence: 99%
“…Additional studies are needed to better understand the mechanism behind the immunomodulatory action. The oral administration of BC IgG-enriched whey fractions (IgG25+) has the potential to protect against food-borne infections ( Salmonella enterica serovar Enteritidis, Enterohaemorrhagic Escherichia coli O1 57:H7, Mycobacterium avium ) and was also found to be partially effective against respiratory tract infection in mice [ 120 ]. Sanctuary et al [ 30 ] reported that the supplementation of bovine colostrum oligosaccharides with Bifidobacterium longum subspecies Infanti 0.3 g twice/day for 12 weeks to children of age 2–11 years suffering from gastrointestinal symptoms and autism disorders results in improvement of gastrointestinal (GI) symptoms and is well-tolerated with a mild gassiness as a common side effect.…”
Section: Current Evidence Of Therapeutic Use Of Bcmentioning
confidence: 99%
“…Several reports that indicate bovine IgG has antibodies against various bacterial antigens and activates the human immune system to repel pathogens have been reviewed ( Ulfman et al, 2018 ). Bovine IgG fraction was reported to protect mice against food-borne infections with enterohaemorrhagic E. coli O157:H7 and Salmonella enterica serovar Enteritidis ( Funatogawa et al, 2019 ). This IgG fraction partially protected mice against respiratory tract infection with Mycobacterium avium (Funatogawa, Tada, Kuwahara-arai, Kirikae, & Takahashi, 2019).…”
Section: Introductionmentioning
confidence: 99%